Hardy breed - Lutz, Giles A (Doubleday & Co Garden City, New York, 1966)
In the early nineteenth century, the Louisiana Purchase opened vast regions of land to Americans. Sparsely populated and far from the center of government in Mexico City, the area of Texas that was purchased attracted large numbers of the daring and the lawless. It was here that Haden Edwards chose a site for his new colony, which he called Fredonia. From the beginning, Edwards and his colonists ran into conflict with the criminal element and corrupt Mexican officials who controlled the land. Unfortunately, Edwards had already earned himself a bad reputation in other sections of Texas, so he didn't have many allies. That left the colonists of Fredonia standing alone against an increasingly powerful band of outlaws. War between these factions was inevitable ... Based on a true historical incident, The Hardy Breed is a dramatic saga of an ill-fated early American attempt to colonize Texas
32272
Keywords: Western; Law enforcement; Outlaws; Historical fiction; Texas